CURRENT STATE OF THE PROBLEM OF TEACHING LESSON DESIGN AND ANALYSIS FOR FUTURE TEACHERS (Academicia Globe: Inderscience Research, 2022)
Education is today one of the key resources that ensure economic growth and prosperity of countries, while in the future the importance of this factor, as the world experience shows, will continuously increase. That is why in all developed countries much attention is paid to the problems of the functioning and development of the national system of general secondary education. The article examines the essence of school education, the development and theoretical justification and a unified approach to teaching students how to design and analyze a lesson as procedures of a research nature, and to create a system of work to teach students these professionally significant skills based on a systematic approach.